Institutions and market integration: The case of coffee in the Ethiopian commodity exchange - Hernandez, Manuel A.; Rashid, Shahidur; Lemma, Solomon; Kuma, Tadesse (International Food Policy Research Institute, 2015)
While the Ethiopian Commodity Exchange (ECX) is widely credited to be a successful on several accounts, there has been little rigorous empirical investigation. This paper attempts to fill that gap by analyzing how ECX has influenced the international-domestic price relationships of coffee—the largest traded commodity on its floor. We examine three aspects of price dynamics—market interdependence, volatility transmission, and structural breaks—using a spatially disaggregated prices of five coffee varieties. The results indicate that contrary to popular media stories, ECX’s success in improving coffee price relationships has been limited. The results appear to be robust under all three sets of analysis.